News grazers media, politics, and trust in an information age - Forgette, Richard (CQ Press, 2019)
KEY FEATURES: Coverage of the media's effects on the 2016 election encourages students to discuss the election while taking into account the broader theoretical concerns about changing news consumption habits and declining political trust. The chapter on partisan news helps students understand the impact of politically polarized news audiences. The chapter on fake news offers students current examples of the political impact of this phenomenon. Examples of the ways in which Americans increasingly have become news grazers show students how growing media choice has transformed how we gather news and is resulting in an increasingly distracted news audience. Discussions about the development of commentary news show how producers have combined drama, opinion, immediacy, and entertainment with straight news content - allowing students to see the impact that this form of news has on the public's trust in Congress and the media.